2016
DOI: 10.1002/jbmr.3002
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes and Risk of Hip Fractures and Non-Skeletal Fall Injuries in the Elderly: A Study From the Fractures and Fall Injuries in the Elderly Cohort (FRAILCO)

Abstract: Questions remain about whether the increased risk of fractures in patients with type 2 diabetes (T2DM) is related mainly to increased risk of falling or to bone-specific properties. The primary aim of this study was to investigate the risk of hip fractures and non-skeletal fall injuries in older men and women with and without T2DM. ) predicted non-skeletal fall injury. The same pattern was found regarding other fractures (any, upper arm, ankle, and major osteoporotic fracture) but not for wrist fracture. Subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 28 publications
4
87
0
8
Order By: Relevance
“…The 'Fractures and fall injuries in the elderly cohort' (FRAILCO, [13]) is a national cohort based on information from several Swedish national registers, linked in order to study associations regarding fractures, fall injuries, morbidity, mortality and medications. Patients were initially selected from the Senior Alert register, consisting of men and women ≥65 years, who underwent a fall risk assessment in connection to a visit to a healthcare facility in Sweden between 2008 and 2014 [14].…”
Section: Study Populationmentioning
confidence: 99%
“…The 'Fractures and fall injuries in the elderly cohort' (FRAILCO, [13]) is a national cohort based on information from several Swedish national registers, linked in order to study associations regarding fractures, fall injuries, morbidity, mortality and medications. Patients were initially selected from the Senior Alert register, consisting of men and women ≥65 years, who underwent a fall risk assessment in connection to a visit to a healthcare facility in Sweden between 2008 and 2014 [14].…”
Section: Study Populationmentioning
confidence: 99%
“…Some of this risk might be captured by insulin use. In a recent report ( N = 429,313) it was shown that T2D patients regardless of medical regimen are more likely to fall than nondiabetics, but hip fractures were only increased in insulin users (HR 1.24 (95% CI: 1.16 1.32)) . This suggests that a mechanism that affects bone strength (e.g., insulin use or diabetes complications) in addition to falls likely plays a role in the increased fracture risk.…”
Section: What Accounts For the Higher Fracture Risk In T1d And T2d?mentioning
confidence: 99%
“…It was revealed that the number of females (54.73%) was higher than the number of males (45.26%) among subjects with hip fracture. Thus, females had higher risk of hip fracture than males on comparing to the control group (Wallander et al) 13 Increased rate of hip fracture is in women which could be because of osteoporosis found commonly after attaining the menopausal age because of hormonal changes.…”
Section: Resultsmentioning
confidence: 99%